Answer to Question #210354 in Differential Equations for Uzair Mughal

Question #210354

xdy + (y-x^2y^2)dx = 0


1
Expert's answer
2021-07-16T03:27:27-0400
"y'+\\dfrac{1}{x}y=xy^2"

First order Bernoulli ODE


"t=y^{1-n}=y^{1-2}=y^{-1}"

"y=t^{-1}, y'=-t^{-2}t'"

"-t^{-2}t'+\\dfrac{1}{x}t^{-1}=xt^{-2}"

"-t'+\\dfrac{1}{x}t=x"

"\\mu=\\dfrac{1}{x}"

"-\\dfrac{1}{x}t'+\\dfrac{1}{x^2}t=1"

"(\\dfrac{1}{x}t)'=\\dfrac{1}{x}t'-\\dfrac{1}{x^2}"

"(\\dfrac{1}{x}t)'=-1"

"\\dfrac{1}{x}t=-x+c_1"

"t=-x^2+c_1x"

"y=\\dfrac{1}{-x^2+c_1x}"


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog